2019
DOI: 10.1039/c8nr05520c
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-responsive lipid-based magnetic nanovectors increase apoptosis in glioblastoma cells through synergic intracellular hyperthermia and chemotherapy

Abstract: TMZ-loaded lipid-based magnetic nanovectors induce apoptosis in U-87 MG cells after magnetothermal stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 44 publications
7
87
0
Order By: Relevance
“…Another studies in vitro using U-87MG cells and employing multiple MHT applications, used SPION with 106.2 nm of diameter submitted to AMF (750 kHz; 200 Gauss), and four days of MHT applications (1 per day during 2 h) showing 50% efficiency after the first MHT application and 80% after three days indicating the importance of latency period for MHT therapeutic efficacy analysis [30]. The precaution adopted in our study of two days latency for MHT efficiency analysis, was very important, because during this latency period it is possible the occurrence of cell death by membrane permeabilization or rupture, increased reactive oxygen species or heat shock protein (Hsp) expression [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another studies in vitro using U-87MG cells and employing multiple MHT applications, used SPION with 106.2 nm of diameter submitted to AMF (750 kHz; 200 Gauss), and four days of MHT applications (1 per day during 2 h) showing 50% efficiency after the first MHT application and 80% after three days indicating the importance of latency period for MHT therapeutic efficacy analysis [30]. The precaution adopted in our study of two days latency for MHT efficiency analysis, was very important, because during this latency period it is possible the occurrence of cell death by membrane permeabilization or rupture, increased reactive oxygen species or heat shock protein (Hsp) expression [32].…”
Section: Discussionmentioning
confidence: 99%
“…These variations have lead to difficulties in finding comparative parameters for results normalization, which requires analysis of specific absorption rate (SAR) and calibration protocols to establish a precise metrological index [27]. Thus, there is no consensus in most GBM in vivo studies for the best condition for MHT application, nor the reason for performing this therapy in multiple applications [13][14][15][22][23][24][25][26][28][29][30]. Variation in the number of MHT applications, its configurations, and the period for tumor evaluation are important aspects that need to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Tapeinos et al [194] Preclinical Human GBM (U87-MG) Lipid-based magnetic nanovectors (LMNVs) Babincova et al [195] Preclinical Human GBM (U87-MG) Etoposide-carrying human serum albumin immobilized magnetic nanoparticles Babincova et al [191] Preclinical Rodent glioma (C6) Thermosensitive magnetoliposomes containing SPIONs and doxorubicin Jia et al 2018 [189] Preclinical Human GBM (U251) RGE-modified, SPION-, and Cur-loaded exosomes (RGE-Exo-SPION/Cur) Lu et al [188] Preclinical Human GBM (U251) Cetuximab (C225)-encapsulated core-shell Fe 3 O 4 @Au magnetic nanoparticles Nguyen et al [173] Preclinical Human GBM (U87-MG) Fluorescently labeled MPIC micelles (G1@Fe 3 O 4 ) Shirvalilou et al [168] Preclinical Rodent glioma (C6) 5-Iodo-2-deoxyuridine (IUdR)-loaded magnetic nanoparticles (NGO/PLGA) Zhou et al, 2018 [187] Preclinical Human GBM (U87-MG) c(RGDyK) peptide PEGylated Fe@Fe 3 O 4 nanoparticles (RGD-PEG-MNPs) Alphand ery et al [175,176] Preclinical Human GBM (U87-MG-Luc) Magnetosomes (CM) Hamdous et al [177] Preclinical Rodent glioma (GL261 þ RG2); Chitosan (M-Chi), polyethyleneimine (M-PEI), and neridronate (M-Neri) coated nanoparticles Le Fevre et al [174] Preclinical Rodent glioma (GL261) Magnetosomes-poly-L-lysine (M-PLL) and iron oxide nanoparticles Ohtake et al [196] Preclinical Human GBM (U87-MG þ U251 þ YKG) Fe(Salen) nanoparticles Zamora-Mora et al [192] Preclinical Human GBM (A-172) Chitosan nanoparticles (CSNPs) Liu et al [169] Preclinical Human GBM (U87-MG) Ferromagnetic IMO nanoflowers (FIMO-NFs) Shevstov et al [185] Preclinical Rodent glioma (C6) Superparamagnetic iron oxide nanoparticles conjugated with heat shock protein (Hsp70-SPIONs) Pala et al [186] Preclinical Human GBM (U87-MG) Dextran-coated, aptamer-bound, aptamer-fluorescein magnetic NPs (NPAF) Yi et al [162] Preclinical Rodent glioma (C6) Magnetic nano-iron Jiang et al [178] Preclinical Human GBM (U251) Silver nanoparticles (AgNPs) Meenach et al [250] Preclinical Human GBM (M059K) Magnetic PEG-based hydrogel nanocomposites Zhao et al [197] Preclinical Human GBM (U251) Solar-planet structured magnetic nanocomposites (Amino silane coated magnetic nanoparticles) Hua et al [198] Preclinical Rodent glioma (C6) Polymer poly[aniline-co-N-(1-one-butyric acid) aniline] (SPAnH) coated iron oxide nanoparticles Liu et al [179] Preclinical Human GBM (U251); Rodent glioma (C6) Silver nanoparticles (Ag...…”
Section: Mhtmentioning
confidence: 99%
“…Alternating magnetic field, which can trigger TMZ release from a lipid-based magnetic NM, and whose therapeutic activity against U87MG cells is enhanced by mild heating at 43 • C under these conditions of excitation [42].…”
mentioning
confidence: 99%
“…A final consideration concerns apoptosis, a mechanism of cellular death that could be weakened among GBM tumor cells, possibly making these cells resistant to standard treatments [123]. With the help of nanoparticulate systems, it has been shown that apoptosis could be restored, for example by heating magnetic nanoparticles in the presence of GBM cancer cells under the application of an alternating magnetic field at mild temperatures of 40-50 • C [1,16,42].…”
mentioning
confidence: 99%